Political change and public culture in post-1990 Nepal - Hutt, Michael; Onta, Pratyoush R. (Cambridge University Press, 2017)
"Discusses how the public meanings of political and social events and developments in post-1990 Nepal have been constructed, conveyed and consumed"--